The post-war overview on self-education - Józef Kargul (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
The paper presents a critical review of the positions on self-education in Poland after World War II. In conclusion, the author hypothesizes that there exist two types of people engaged in self-education. One type is applied to those who commit themselves to self-education in order to become similar to specific pattern and those people are referred to as "other-directed"; another one refers to people taking self improvement (in all sides of their own personality) to efficiently perform tasks that life puts in front of them (inner-directed).